Photovoltaic emulator of different solar array configurations under partial shading conditions using damping injection controller - Mustapha Alaoui; Hattab Maker; Azeddine Mouhsen; Hicham Hihi (Institute of Advanced Engineering and Science, 2020)
In the last decades, researchers and scientists have been trending towards photovoltaic (PV) solar energy research as one of the noteworthy renewable energies. As a matter of fact, the need for a laboratory system devoted to performing measurements and experimentation on PV systems is being increased. The PV array emulator is designed to accomplish this task by reproducing accurately the electrical behavior of real PV sources. The present paper proposes thus a new control and design of PV array emulators. It is based essentially on a hybrid Damping Injection controller. The proposed control strategy circumvents obviously the existing PV emulator's limitations in terms of accuracy, speed and partial shading emulation. Several results are given and discussed to show the efficiency of the proposed system to emulate PV modules and different PV array configurations under uniform solar irradiance and partial shading conditions.